2021
DOI: 10.1002/env.2697
|View full text |Cite
|
Sign up to set email alerts
|

A self‐exciting marked point process model for drought analysis

Abstract: A self‐exciting marked point process approach is proposed to model clustered low‐flow events. It combines a self‐exciting ground process designed to capture the temporal clustering behavior of extreme values and an extended Generalized Pareto mark distribution for the exceedances over a subasymptotic threshold. The model takes into account the dependence between the magnitude and occurrence time of exceedances and allows for closed‐form inference on tail probabilities and large quantiles. It is used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Hawkes processes or self‐exciting processes, first introduced by Hawkes (1971a, 1971b), are counting processes often used to model the “arrivals” of some events over time, when each arrival increases the probability of subsequent arrivals in its proximity. Typical applications can be found in seismology (Ogata, 1988, 2011; Ogata & Zhuang, 2006; Schoenberg, 2022), capture‐recapture (Altieri et al, 2022; Weller et al, 2018), invasive species (Balderama et al, 2012), droughts (Li et al, 2021), crime (Mohler, 2013; Mohler et al, 2011, 2018), finance (Azizpour et al, 2018; Filimonov & Sornette, 2012; Hawkes, 2018), disease mapping (Chiang et al, 2022; Garetto et al, 2021), wildfires (Peng et al, 2005), and social network analysis (Kobayashi & Lambiotte, 2016; Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Hawkes processes or self‐exciting processes, first introduced by Hawkes (1971a, 1971b), are counting processes often used to model the “arrivals” of some events over time, when each arrival increases the probability of subsequent arrivals in its proximity. Typical applications can be found in seismology (Ogata, 1988, 2011; Ogata & Zhuang, 2006; Schoenberg, 2022), capture‐recapture (Altieri et al, 2022; Weller et al, 2018), invasive species (Balderama et al, 2012), droughts (Li et al, 2021), crime (Mohler, 2013; Mohler et al, 2011, 2018), finance (Azizpour et al, 2018; Filimonov & Sornette, 2012; Hawkes, 2018), disease mapping (Chiang et al, 2022; Garetto et al, 2021), wildfires (Peng et al, 2005), and social network analysis (Kobayashi & Lambiotte, 2016; Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…see Blanchet et al, 2018;Evin et al, 2018;Naveau et al, 2016;Taillardat et al, 2019;Taillardat & Mestre, 2020;Tencaliec et al, 2020), to model the river discharges (e.g. see Li et al, 2021), the daily temperature maxima (e.g. see Stein, 2021b), the wind speed (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Hawkes point process model (Hawkes, 1971), a type of branching point process model, has been used for a wide variety of applications, including seismology (Adelfio & Chiodi, 2008; Chiodi & Adelfio, 2011; Molyneux et al, 2018; Nichols & Schoenberg, 2014; Ogata, 1998; Siino et al, 2019), invasive species (Balderama et al, 2012), disease epidemics (Meyer et al, 2012), reported crimes (Mohler et al, 2011), drought events (Li et al, 2021), terrorist attacks (Clauset & Woodard, 2013), financial events (Bacry et al 2015). Hawkes models have long been used in seismology to describe the rate of aftershock activity following an earthquake (Ogata, 1988; Ogata, 1998) and have outperformed alternatives for earthquake forecasting (Gordon et al, 2015; Zechar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%